Evolution of Self: Exploration of Personality Development in Kamila Shamsie's Selective Novel (Journal of Social Sciences Review, 2023)
The persona of Hasan in Kamila Shamsie’s novel In the City By the Sea is a complicated and multi-faceted character whose adventure from childhood to adulthood illustrates his cognitive and psychosocial improvement in the story. In this paper, we have analyzed Hasan's character focusing on his cognitive maturity and social development, discovering through his life experiences and relationships his idea of self and the world around him. Our discussion draws on Jean Piaget's theory of cognitive development, explaining the ways Hasan's conception of reality and truth undergoes evolution over time as he progresses from a concrete, sensorimotor awareness of the world to greater abstract, formal operational understanding. We additionally utilize Erikson's ideas on psychosocial development, especially the stage of identity versus identity confusion in his theory and the blossoming of Hasan's ego identity. The paper argues that Hasan's immediate life experiences and relationships play an essential function in shaping his idea of himself and the surrounding world. In conclusion, our research offers an insightful interpretation of Hasan's portrayal in the novel, exploring the functioning of cognitive and psychosocial growth at work in his progression from formative years to maturity. The current research highlights the utility of Piaget and Erikson's theories to interpret literary characters and unpack the interplay of both nature and nurture in comprehending the complex phenomenon of human development.
Keywords: Kamila Shamsie; Pakistani Literature in English; Cognitive Development; Psychosocial Development; Novel